2018
DOI: 10.1051/0004-6361/201834218
|View full text |Cite
|
Sign up to set email alerts
|

Generalised model-independent characterisation of strong gravitational lenses

Abstract: In galaxy-galaxy strong gravitational lensing, Einstein rings are generated when the lensing galaxy has an axisymmetric lensing potential and the source galaxy is aligned with its symmetry centre along the line of sight. Using a Taylor expansion around the Einstein radius and eliminating the unknown source, I derive a set of analytic equations that determine differences of the deflection angle of the perturber weighted by the convergence of the axisymmetric lens and ratios of the convergences at the positions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 50 publications
(89 reference statements)
2
67
0
Order By: Relevance
“…That the source plane offset has no direct meaning can also be seen by noticing that both a given lensing potential ψ0(θ) and ψ1(θ) = ψ0(θ) + a · θ (A1) correspond to the same images and mass density, but with a shift in source plane (Seitz et al 1998). This can be seen to be a special case of the more general equation (21) in Wagner (2018) which shows the change in potential that corresponds to a shift in source plane position.…”
Section: Appendix A: Source Position Offsetsmentioning
confidence: 95%
See 1 more Smart Citation
“…That the source plane offset has no direct meaning can also be seen by noticing that both a given lensing potential ψ0(θ) and ψ1(θ) = ψ0(θ) + a · θ (A1) correspond to the same images and mass density, but with a shift in source plane (Seitz et al 1998). This can be seen to be a special case of the more general equation (21) in Wagner (2018) which shows the change in potential that corresponds to a shift in source plane position.…”
Section: Appendix A: Source Position Offsetsmentioning
confidence: 95%
“…It was soon found to be a special case of several classes of invariance transformations that leave the observables in multiple-image configurations invariant (Gorenstein et al 1988a;Schneider & Sluse 2014). Making the lens reconstruction independent of specific (parametric) lens models, it was found that these degeneracies that had been treated as global transformations of the entire lens and source plane properties, can be further generalised, such that they locally apply to each system of multiple images individually (Liesenborgs et al 2008a;Liesenborgs & De Rijcke 2012;Wagner 2018). It is clear that these degeneracies cause difficulties in constraining the mass density of a specific lensing object at a certain redshift from such lensing observations, with the integration of mass along the line of sight further confounding the issue (Wagner 2019).…”
Section: Gravitational Lensing Formalismmentioning
confidence: 99%
“…Equation (31) implies a degeneracy between the deflection angle of the perturber and the convergence of the axisymmetric lens. As further detailed in [24], this degeneracy can be interpreted as an exact source-position transformation, introduced in [75]. As explained in [27], this degeneracy originates from an a priori arbitrary split of the total deflection potential into a main lens and a perturber.…”
Section: The Giant-arc Casementioning
confidence: 99%
“…[62] already described the possibility to extract the local lens properties contained in A(x) by transforming multiple images onto each other. In [23,47], we realised this idea for unresolved and resolved multiple images that contain at least two non-parallel vectors, as indicated by the black arrows in the figures of Table 1. We assume to have m reference points within each multiple image i which are located at positions x iα , α = 1, ..., m. Using the quadrupole of an unresolved image as observables, the three reference points are the centre of light and the end points of the semi-major and semi-minor axis of the quadrupole.…”
Section: Local Lens Properties From a Taylor Expansion Around The Cenmentioning
confidence: 99%
See 1 more Smart Citation